Ran GTPase cycle: one mechanism - two functions - Melchior, Frauke (Current biology, 2001)
The Ras-related GTPase Ran functions in nucleocytoplasmic transport by regulating interactions of transport receptors with transport cargo. Three recent studies suggest that Ran uses exactly the same mechanism to regulate spindle assembly during mitosis.